Politics of memory in 2001 Salento. The re-invention of tarantism and the debate on its therapeutical value - Pizza, Giovanni (AM. Rivista della Società Italiana di Antropologia Medica, 2002)
Politics of memory in 2001 Salento. The re-invention of tarantism and the debate on its therapeutical value